Indikator Kebutuhan Perawatan Ortodonsia (IKPO) sebagai Instrumen Perencanaan Pelayanan Ortodonsia - Faruk Hoesin (Faculty of Dentistry, Universitas Indonesia, 2015)
Children are a nation's greatest inheritance shaping the country's future. In Indonesia, it is estimated that almost 40% of the population or around 85 million are children who are in their developing years. One of a parents' roles is to observe that their children's dental structure is growing suitably for their gae. Most parents have a concern that their children have (or will have) a malocclusion or malposition caused by combined features of disharmony in their teeth. Such a disharmony will affect the overall facial structure developemnt process, e.g. in the jaw, facial bones and soft tissues such as lips, cheeks and even the tonue. Should each condition occur on a chiled, it may have a negative psychological effect on a growing child, such as causing low self-esteem. A child's dental development needs parents' special attention as it concerns their overall dental health. On the other hand, many parents do not have proper knowledge of the normal dental growth/development. In case of abnormal development the parents should at least know whether or not their child needs orthodontic care. With the Orthodontic Treatment Needs Indicator (OCNI) the parents can easily determine at an early stage whether or not the child needs to have an orthodontic treatment. The OCNI involves a set of questions to parents and child regarding the child's dental development, and has a simple self-assessment-based scoring with the help of a denist as consultant. An OCNI score intends to achieve a better orthodontic treatment process for the potential patient, to improve the quality of the child's dental health and to achieve healthy and productive teeth.